Hanna Kupś, Maciej Szatkowski, Michał Dahl (Eds.). 70 lat Chińskiej Republiki Ludowej w ujęciu interdyscyplinarnym, Warszawa 2021, pp. 309 - Mruk, Marzena (Historia i Polityka, 2021)
Review of Hanna Kupś, Maciej Szatkowski, Michał Dahl (Eds.). 70 lat Chińskiej Republiki Ludowej w ujęciu interdyscyplinarnym, Warszawa 2021, pp. 309.